1985
DOI: 10.1210/endo-117-4-1490
|View full text |Cite
|
Sign up to set email alerts
|

A Monoclonal Antibody to a Mammary Cell Line Recognizes Two Distinct Subtypes of Ovarian Granulosa Cells*

Abstract: When screening supernatant fluids from hybridoma clones, Dulbecco and co-workers found that a mouse monoclonal antibody generated against a mammary tumor cell line showed rather striking high binding to rat oocytes and granulosa cells. In this study we have specifically investigated the reactivity of the monoclonal antibody (designated anti-OA-1) with granulosa cells during the differentiation process. This was accomplished using the two-step indirect immunocytochemical technique. When a primordial follicle is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

1986
1986
2012
2012

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…This heterogeneity in the fate of the follicles after withdrawal of gonadotrophin support has also been described for barbiturate-blocked rats (Braw & Tsafriri, 1980), since ovulatory efficiency in response to hCG decreased from 88 to 70, 52 and 31% after 1, 2, 3 and 4 days of blockade. This might be linked to the between-follicle balance in the different subtypes of granulosa cells (Erickson et al, 1985;Kasson et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…This heterogeneity in the fate of the follicles after withdrawal of gonadotrophin support has also been described for barbiturate-blocked rats (Braw & Tsafriri, 1980), since ovulatory efficiency in response to hCG decreased from 88 to 70, 52 and 31% after 1, 2, 3 and 4 days of blockade. This might be linked to the between-follicle balance in the different subtypes of granulosa cells (Erickson et al, 1985;Kasson et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The density of the endocrine receptors and the intensity of steroidogenesis are higher in the outer layer, whereas the proliferative activity is higher in the inner oocyteassociated layer (Erickson et al 1985;Amsterdam et al 1989;Vanderhyden and Macdonald 1998). Only cumulus cells expand by "mucification".…”
Section: Introductionmentioning
confidence: 99%
“…By analyzing these antigens, numerous new regulatory mechanisms of differentiation have been revealed. In the field of ovarian research, Alila and Hansel [1] [2,3] reported two mAbs (OA-1 and OA-2) raised against a rat mammary tumor cell line. Although their expression was not specific to granulosa cells in the ovary, the antigen expression profiles on gran ulosa cells were related to the differentiation state, sug gesting the usefulness of mAbs to analyze ovarian follicu lar differentiation.…”
Section: Introductionmentioning
confidence: 99%